Individual Educational Trajectory as Intention of Subject in Continuing Education System - E. F. Zeer; D. P. Zavodchikov; M. V. Zinnatova; E. V. Lebedeva (Научный диалог, 2017)
The issue of improving the quality of education by developing individual educational trajectories is considered. The relevance of this topic is determined by the necessity to predict the development of personality in a changing vocational and educational space. The definitions of “individual educational trajectory” concept in the context of the continuing education system and educational environment of university are given. Attention is given to the need to conform the goals, objectives, content, forms and methods of continuing education to the need of conscious self-realization of personality in the projecting and implementation of his/her own trajectory in dynamic, asymmetric, open, undefined terms of socio-professional life. It is argued that the forms of sense generating and skills of designing and forecasting his/herself in professional future may be envisioned through accompanying, navigation activity corresponding to the needs and content of the stages of professional formation. The stages of professional development, event forms of continuing education and the basic psychological neoplasms arising in the process of professionalization are correlated. The conditions and predictors of construction of individual educational trajectories are analysed. It is concluded that vocational education should be human-like systems, which effectiveness criterion should be not actual economic feasibility, but the ability to form the personality and willingness to self-realization in a complex, dynamic world of the professions.